Analytical Solution of Tidal Loading Effect in a Submarine Leaky Confined Aquifer System. (20th June 2019) - Song, Zongzhong; Li, Hailong; Ma, Qian; Zheng, Chunmiao; Jiao, Jiu Jimmy; Li, Shaohong
Abstract : Although there are many existing analytical studies of tidal groundwater level fluctuations in coastal aquifer systems, few of them focus on an offshore submarine aquifer. Here, we consider tidal groundwater head fluctuations in a submarine leaky confined aquifer overlain by a semipermeable seabed. Both the seabed and the confined aquifer are assumed to extend horizontally infinitely. A one-dimensional mathematical model is established to describe the problem, and the analytical solution is derived. The impacts of the tidal loading efficiency, hydraulic conductivity and elastic storage of the semipermeable layer and aquifer on the groundwater head fluctuations in the aquifer system are analyzed and discussed. Solution analyses indicated that tidal loading effects tend to enhance the amplitude of the tidal groundwater fluctuation in the confined aquifer system and to reduce the phase shift between the groundwater head and the sea tide fluctuations.